Morrer no domicílio: fatores associados à satisfação da preferência do doente - Ferreira, Rita Carvalho Cunha (2022)
Background: Place of death has been studied and acknowledged as relevant in palliative care. In Portugal, it seems that most patients prefer to die at home, although that preference is not satisfied. Aim: Identify the factors related to satisfying patients’ preference to die at home among palliative care recipients in Portugal. Methods: An epidemiologic, observational, cross-sectional, and analytic study was performed in patients treated during 2017 in palliative care facilities that answered a research work conducted by the Portuguese Observatory for Palliative Care. A set of independent variables concerning demographic, social, clinical, and healthcare characterization was selected. Chi-Square and Mann-Whitney tests and a binary logistic regression model were employed for the bivariate statistical analysis. The multivariate analysis was performed by using a logistic regression model based on the Forward method considering the Wald test. Results: We obtained a 9.8% response rate from the institutions, which included 68 patients. 52.9% were male and the median age was 78.5 (IQR=19). The preference to die at home was met in 32.3% (k=0.26). We found statistically significant as sociations with residence in theAzores (OR=3.79), and in rural areas (OR=10.00), duration of follow up in a palliative care team (≤ 30 days, OR=0.15), and assistance by home palliative care teams (OR=9.00). Conclusions: We obtained a fair satisfaction degree of patients’ preference to die at home, with one of the lowest values ob served in the literature.We identified an association with place of residence, duration of follow-up in palliative care, and assis tance by home specialized teams. These enabling factors agree with those previously reported in other international studies. They should guide strategies definition adjusted to the reality of the Portuguese population.